Racial inequality and school failure of black students - Ladislau Ribeiro do Nascimento (Universidade Federal do Norte do Tocantins, 2019)
This article proposes a reflection on the importance of considering racial inequality as a phenomenon linked to school failure. The text is based mainly on references produced in the interface between psychology and education. At first, school failure was approached as a complex phenomenon, produced and reproduced from the influence of forces caused in the political, economic, social and institutional fields. Next, we sought to highlight the connections between racial and social inequality and the production of school failure, and to analyze the correlation between stigma, invisibility and silencing of black students. Finally, we considered the need to address the problem of racial inequality more effectively in understanding and coping with school failure.